Effect of developmental stress on the in vivo neuronal circuits related to excitation–inhibition balance and mood in adulthood - Oh, Se Jong; Lee, Namhun; Nam, Kyung Rok; Kang, Kyung Jun; Lee, Kyo Chul; Lee, Yong Jin; Seok, Jeong-Ho; Choi, Jae Yong (Frontiers in Psychiatry, 2023)
Traumatic events in early life have a deleterious effect on the development of normal brain developments, which may be a cause of various psychiatric disorders in adulthood. Most prior studies focused on molecular biological aspects, and research on functional changes in neural circuits is still limited. We aimed to elucidate the effect of early life stress on in vivo excitation-inhibition and serotonergic neurotransmission in the adulthood using non-invasive functional molecular imaging (positron emission tomography; PET). To compare the effect of stress intensity, early life stress animal models were divided into single trauma (MS) and double trauma groups (MRS). MS was derived from maternal separation, whereas MRS was derived from maternal separation and restraint stress after birth. And to evaluate the stress vulnerability on the sex, we used male and female rats. As a results, the MRS group showed greater weight loss and more severe depressive/anxiety-like behaviors than the MS and control groups. Corticosterone levels in MRS showed a greater extent of decline than in the MS group; however, there was no significant difference in the change of T3 and T4 between MS and MRS. In the PET, the stress exposure groups showed lower brain uptake for GABAergic, glutamatergic, and serotonergic systems compared with the control group. The excitatory/inhibitory balance, which was derived by dividing glutamate brain uptake into GABAergic uptake, increased as stress intensity increased. Neuronal degeneration in the stress exposure groups was confirmed by immunohistochemistry. In the sex comparison, female showed the greater changes of body weight, corticosterone level, depressive/anxiety-like behavior, and neurotransmission systems than those in male. Taken together, we demonstrated that developmental stress induces dysfunction of neurotransmission in vivo, and that females are more vulnerable to stress than males.